2014
DOI: 10.1111/anec.12133
|View full text |Cite
|
Sign up to set email alerts
|

Significance and Usefulness of Narrow Fragmented QRS Complex on 12-Lead Electrocardiogram in Acute ST-Segment Elevation Myocardial Infarction for Prediction of Early Mortality and Morbidity

Abstract: Background:The presence of notched R or S waves without accompanying typical bundle branch blocks, or the existence of an additional wave like RSR' pattern in the original QRS complex (with a duration of <120 ms) has been defined as narrow QRS fragmentation. Persistence of the fQRS found on the admission electrocardiogram (ECG) in patients with acute ST segment elevation myocardial infarction (STEMI) will have prognostic significance in the short term.Methods: The study was carried out using retrospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 22 publications
6
35
0
1
Order By: Relevance
“…Although three vessels disease was significantly higher in group 1, there was no such relationship between QRS distortion and three vessels disease, as has been previously reported. 10,21,22 Our study confirms the relationship between fQRS and three vessels disease first reported by Stavileci et al 22 In contrast to our findings, Ari et al 23 reported that there was no relationship between fQRS and three vessels disease. This may be because that study had a lower number of patients (85 patients) and only included patients who underwent primary PCI.…”
Section: Discussionsupporting
confidence: 90%
“…Although three vessels disease was significantly higher in group 1, there was no such relationship between QRS distortion and three vessels disease, as has been previously reported. 10,21,22 Our study confirms the relationship between fQRS and three vessels disease first reported by Stavileci et al 22 In contrast to our findings, Ari et al 23 reported that there was no relationship between fQRS and three vessels disease. This may be because that study had a lower number of patients (85 patients) and only included patients who underwent primary PCI.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of fQRS has been demonstrated to be an independent predictor of impaired myocardial perfusion and left ventricular function detected by myocardial single-photon emission computed tomography imaging in patients with ischemic heart disease [9,22,23]. Moreover, fQRS, which may be widened or narrowed, has been reported to be related with a high incidence of major adverse cardiovascular events, including mortality due to hemodynamically significant ventricular arrhythmic events in CAD, acute coronary syndromes [24,25], hypertrophic obstructive cardiomyopathy [26], ischemic and non-ischemic cardiomyopathy [27,28], and decompensated systolic heart failure [29]. Moreover, a significant relation between the presence of wide fQRS and the occurrence of CSF was demonstrated by Yilmaz et al [30].…”
Section: Discussionmentioning
confidence: 99%
“…9-12, 16, 17 Six studies reported in-hospital adverse events, thus it may be assumed that no cases were lost to follow-up. [13][14][15][16][17][18] In addition, it was not clear how three studies accounted for potential confounders, raising the small possibility of result distortion. 13,15,18 The funnel plot did not suggest evidence of publication bias (Fig.…”
Section: Study Qualitymentioning
confidence: 99%
“…[3][4][5][6][7] In addition, various studies have evaluated the prognostic importance of fQRS in patients with acute coronary syndrome (ACS), ST-segment elevation (STEMI), or non-ST segment elevation myocardial infarction (NSTEMI). [8][9][10][11][12][13][14][15][16][17][18] Some recent papers reviewed the clinical importance of fQRS in patients with cardiovascular diseases. [19][20][21] However, the literature regarding the definition and the prognostic value of fQRS in patients with AMI is heterogeneous and the findings are not easy to interpret.…”
mentioning
confidence: 99%